การประเมินการใช้พลังงานสำหรับหัวเผาประสิทธิภาพสูงในเตาชัตเติลของอุตสาหกรรมเซรามิกในประเทศไทย - เสาวรา อาสาวะ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The purpose of this thesis is to analyze and compare the energy consumption of the high efficiency burners, which are the recuperative burner and the regenerative burner, for the shuttle kiln in the ceramic industry.In order to select a type of the high efficiency burner which appropriates for the kiln,the energy data from the shuttle kiln is utilize from the size of 4 cubicmeter and the use of the liquefied petroleum gas (LPG). The project is conducted under the assumptions for a period of 70 years.The energy balanceof the shuttle kilnshowed thatthe thermal efficiency is 32.39%. According to an analysis of the the recuperative burner, the obtained optimum preheating air combustion temperature is700๐C. The fuel consumption of the high efficiency burner can be saved about 30.51%.The Net Present Value (NPV) and the payback period are5,074,855.52Baht,and2.56years, respectively.In the case of the regenerative burner, the obtained optimum preheating air combustion temperature is900๐C. The fuel consumption of the high efficiency burner can be saved about 39.70%.However, the Net Present Value (NPV) is4,911,429.12Baht, which is over than the one from the recuperative burner and the payback period is4.17years which is longer than the one from the recuperative burner. Therefore,the recuperative burner should be invested in this study.